A Vaccine Based on the Receptor-Binding Domain of the Spike Protein Expressed in Glycoengineered Pichia pastoris Targeting SARS-CoV-2 Stimulates Neutralizing and Protective Antibody Responses. (June 2022) - Liu, Bo; Yin, Ying; Liu, Yuxiao; Wang, Tiantian; Sun, Peng; Ou, Yangqin; Gong, Xin; Hou, Xuchen; Zhang, Jun; Ren, Hongguang; Luo, Shiqiang; Ke, Qian; et al.
Abstract: In 2020 and 2021, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus, caused a global pandemic. Vaccines are expected to reduce the pressure of prevention and control, and have become the most effective strategy to solve the pandemic crisis. SARS-CoV-2 infects the host by binding to the cellular receptor angiotensin converting enzyme 2 (ACE2) via the receptor-binding domain (RBD) of the surface spike (S) glycoprotein. In this study, a candidate vaccine based on a RBD recombinant subunit was prepared by means of a novel glycoengineered yeast Pichia pastoris expression system with characteristics of glycosylation modification similar to those of mammalian cells. The candidate vaccine effectively stimulated mice to produce high-titer anti-RBD specific antibody. Furthermore, the specific antibody titer and virus-neutralizing antibody (NAb) titer induced by the vaccine were increased significantly by the combination of the double adjuvants Al(OH)3 and CpG. Our results showed that the virus-NAb lasted for more than six months in mice. To summarize, we have obtained a SARS-CoV-2 vaccine based on the RBD of the S glycoprotein expressed in glycoengineered Pichia pastoris, which stimulates neutralizing and protective antibody responses. A technical route for fucose-free complex-type N -glycosylation modified recombinant subunit vaccine preparation has been established.